Sustainability in Bank: Deposits, Investment and Interest Rate - Josua Panatap Soehaditama (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of the study is to analyze and substantiate the papers on the variables of this study using a literature review. The research method used is a qualitative literature search of scientific papers from various national and internationally renowned journals. A discussion survey found that each of the three variables was derived from the results of presenting literature reviews from dozens of academic papers using indexes of national and prominent journals, and that deposits and banking It was found that there is an effect between and both. How fluctuations in interest rates and investments in banks affect them. There are also differentiating variables discovered by researchers: business model, ownership, accountability, meeting performance, company performance, market discipline, etc